Ticks (Acari: Ixodidae) associated with domestic dogs in Franca region, São Paulo, Brazil - Juan Szabó, Matias Pablo [UNESP]; Marquez Cunha, Tiago; Pinter, Adriano; Vicentini, Fernando (Springer Nature, 2001)
Ticks on 140 domestic dogs from both urban and rural areas of Franca region in São Paulo state were identified with 102 dogs from urban areas and 38 from rural areas. Of urban dogs, 27.5% were infested exclusively by Rhipicephalus sanguineus ticks. Of the rural dogs, 36.8% were infested with the following tick species: R. sanguineus, Boophilus microplus, Amblyomma ovale and A. cajennense. Mixed infestations included a dog hosting A. cajennense and A. ovale and another with B. microplus and R. sanguineus. The most intense infestations were detected on urban dogs. Hemolymph tests of these ticks performed to detect rickettsial or Borrelia bacteria yielded negative results.
Keywords: Brazil; Domestic dog; Franca region; Ixodidae; São Paulo; Tick; domestic species; rural area; tick; urban area; animal; animal disease; dog; dog disease; domestic animal; infestation; insect control; methodology; parasitology; Animals; Animals, Domestic; Dog Diseases; Dogs; Tick Control; Tick Infestations; Acari; Amblyomma; Amblyomma cajennense; Amblyomma ovale; Animalia; Boophilus microplus; Borrelia; Canis familiaris; Canis lupus; Insecta; Rhipicephalus; Rhipicephalus sanguineus